Analysis of the soft switching modes for energy loss measurement of high frequency closed-loop boost converter - Pradhan, Ajoya Kumar; Samal, Sarita; Barik, Prasanta Kumar; Nayak, Smrutiranjan (Institute of Advanced Engineering and Science, 2025)
This manuscript explains the analysis of the soft switching technology to measure the energy loss of high-frequency closed loop boost converter with zero-current switching (ZCS) and zero-voltage switching (ZVS) techniques. To get these attributes, the use of soft power converters that utilize soft switching techniques is essential. This paper examines the ZCS/ZVS AC/DC converter design, used in high-power systems for renewable energy and battery charging. This converter architecture ensures semiconductor switches turn on and off at zero voltage and current. It smooths rectifier diodes, reducing switching and reverse recovery losses. It has better power quality, efficiency, and input power factor. Practical study has been done to verify the converter's theoretical analysis. Empirical research shows gentle switching enhances system efficiency. Energy losses are reduced by 26% while turning on and 20% when turning off compared to the ZVS and ZCS. The prototype converter is built to corroborate simulation results. Compared to ZVS and ZCS, switching losses are lower and efficiency decline is modest across the operating range. This shows that the simulation and experimental results are consistent.